Kinetics of the B- and T-Cell Immune Responses After 6 Months From SARS-CoV-2 mRNA Vaccination in Patients With Rheumatoid Arthritis - Farroni, Chiara; Picchianti-Diamanti, Andrea; Aiello, Alessandra; Nicastri, Emanuele; Laganà, Bruno; Agrati, Chiara; Castilletti, Concetta; Meschi, Silvia; Colavita, Francesca; Cuzzi, Gilda; Casetti, Rita; Grassi, Germana; et al. (Frontiers in Immunology, 2022)
Objective: To assess the kinetic of the humoral and cell-mediated responses after SARS-CoV-2 vaccination in rheumatoid arthritis (RA) patients treated with different immunosuppressive therapies. Methods: Following vaccine completed schedule, Health Care Workers (HCWs, n=49) and RA patients (n=35) were enrolled at 5 weeks (T1) and 6 months (T6) after the first dose of BNT162b2-mRNA vaccination. Serological response was assessed by quantifying anti-Receptor Binding Domain (RBD) specific IgG and SARS-CoV-2 neutralizing antibodies, while cell-mediated response by a whole blood test quantifying the interferon-(IFN)-γ response to spike peptides. B-cell phenotype and IFN-γ-specific T-cell responses were evaluated by flow cytometry. Results: After 6 months, anti-RBD antibodies were still detectable in 91.4% of RA patients, although we observed a significant reduction of the titer in patients under CTLA-4-Ig (median: 16.4 BAU/mL, IQR: 11.3-44.3, p<0.0001) or TNF-α-inhibitors (median: 26.5 BAU/mL, IQR: 14.9-108.8, p=0.0034) compared to controls (median: 152.7 BAU/mL, IQR: 89.3-260.3). All peripheral memory B cells (MBCs) subpopulations, in particular the switched IgG+ MBCs (CD19+CD27+IgD-IgM-IgG+), were significantly reduced in RA subjects under CTLA-4-Ig compared to HCWs (p=0.0012). In RA patients, a significant reduced anti-RBD IgG titer was observed at T6 vs T1, mainly in those treated with CTLA-4-Ig (p=0.002), IL-6-inhibitors (p=0.015), and DMARD+/-CCS (p=0.015). In contrast, a weak not significant reduction of the T-cell response was reported at T6 vs T1. T-cell response was found in 65.7% of the RA patients at T6, with lower significant magnitude in patients under CTLA-4-Ig compared to HCWs (p<0.0001). The SARS-CoV-2 IFN-γ-S-specific T-cell response was mainly detected in the CD4+ T-cell compartment. Conclusions: In this study, we provide evidences of the kinetics, waning and drug-induced impairment showing a significant reduction of the humoral and, to a less extent, of the T-cell response after 6 months of completed COVID-19 vaccination in RA patients. Similarly, a reduction of the specific response was also observed in the controls. Therefore, based on these results, a booster dose of the vaccine is crucial to increase the specific immune response regardless of the immunosuppressive therapy.